The role of profitability in mediating company ownership structure and size of firm value in the pharmaceutical industry on the Indonesia stock exchange - Sugosha, Made Jelita; Artini, Luh Gede Sri (International research journal of management, IT and social sciences, 2020)
The purpose of this study was to examine the effect of ownership structure, firm size, and profitability on firm value. The research model was built by placing profitability measured by Return on Equity (ROE) as a mediating variable on the effect of ownership structure and firm size on the firm value measured by Price to Book Value (PBV). The study was conducted on the Pharmaceutical Industry in the Indonesia Stock Exchange for the period 2013-2018, with a total sample of 42 obtained by purposive sampling technique and analyzed by path analysis method. The results showed that foreign ownership had a significant positive effect on profitability but did not have a significant positive effect on firm value. Managerial ownership has no significant positive effect on profitability and no significant negative effect on firm value. Institutional ownership does not have a significant positive effect on profitability and firm value. The firm size has a significant positive effect on profitability but does not have a significant positive effect on firm value. Profitability has a significant positive effect on firm value.